2021
DOI: 10.1121/10.0003930
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on lung ultrasound B-line formation as a function of imaging frequency and alveolar geometries

Abstract: Lung ultrasound (LUS) has become a widely adopted diagnostic method for several lung diseases. However, the presence of air inside the lung does not allow the anatomical investigation of the organ. Therefore, LUS is mainly based on the interpretation of vertical imaging artifacts, called B-lines. These artifacts correlate with several pathologies, but their genesis is still partly unknown. Within this framework, this study focuses on the factors affecting the artifacts' formation by numerically simulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 17 publications
2
39
0
Order By: Relevance
“…Only recently researchers have started to perform studies on LUS in silico. The first study investigated the dependence of vertical artifacts on alveolar diameter and spacing (i.e., distance between alveoli) (Peschiera et al 2021). The numerical simulations were performed using the k-Wave MATLAB toolbox (Treeby and Cox 2010), which was used to replicate a simplified lung structure.…”
Section: In Silico Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently researchers have started to perform studies on LUS in silico. The first study investigated the dependence of vertical artifacts on alveolar diameter and spacing (i.e., distance between alveoli) (Peschiera et al 2021). The numerical simulations were performed using the k-Wave MATLAB toolbox (Treeby and Cox 2010), which was used to replicate a simplified lung structure.…”
Section: In Silico Studiesmentioning
confidence: 99%
“…The numerical simulations were performed using the k-Wave MATLAB toolbox (Treeby and Cox 2010), which was used to replicate a simplified lung structure. Specifically, the first 2 cm of depth was composed of muscle tissue, whereas air inclusions (alveoli) were introduced beyond 2 cm (Peschiera et al 2021). These alveoli were periodically arranged to maintain the same distance between each other, in both the axial and lateral directions.…”
Section: In Silico Studiesmentioning
confidence: 99%
“…The ratio of male to female patients was 47 : 43. The highest age of the patients was 69 years old, and the lowest was 21 years old, with an average of (40.37 ± 4.36) years old; the longest course of disease was 8 months and the shortest was 3 days, with an average of (45.38 ± 7.25) days [ 11 ]. In the same period, 90 healthy persons were selected as the control group, of which the male to female ratio was 55 : 45.…”
Section: Experimental Analysismentioning
confidence: 99%
“…The frequency response of these bubbly structures is more likely associated to specific resonance phenomena. A subsequent work [ 18 ] by the same group tested the genesis of the artifacts on a laboratory model by reproducing the alveoli shape with the alveolar interstitium level, with known dimensions; the authors showed that low imaging frequencies (i.e., f 2 MHz) generally do not allow the generation of consistent artifacts, regardless of the alveolar diameter choice. Only when the alveolar spacing assumes the largest investigated value (i.e., s 395 lm) do the lowest frequencies start to enable the B-lines’ formation.…”
mentioning
confidence: 99%
“…Therefore, the final representation of the vertical artifact on B-mode ultrasound seems to strongly depend on the frequency of the ultrasounds employed by the probe (therefore on the setting of the machine), and on the three-dimensional structure of the interstitium-alveolar spaces. The authors argued that those factors can affect the representation of the artifacts on the ultrasound image, and in the near future it will be possible to differentiate different pictures of different diseases (with alveolar interstitium involvement) on the basis of the iconographic representation of the vertical artifacts [ 17 , 18 ]. The frequency characterization of vertical artifacts can be used as an indirect measure of the state of the lung, i.e., the lower the frequency at which B lines are visualized, the larger the channels formed between the alveoli and the more severe the lung condition [ 17 , 18 ].…”
mentioning
confidence: 99%